Match Rates, Individual Development Accounts, and Saving by the Poor - Schreiner, Mark (Journal of Income Distribution®, 2005)
Individual Development Accounts (IDAs) provide poor people with matches for savings used for home purchase, post-secondary education, or microenterprise. Match rates for IDAs in the American Dream Demonstration (ADD) were typically 1:1 or 2:1 but ranged as high as 7:1. How did the match rate affect IDA savings? The analysis here controls for a number of confounding factors often ignored in similar studies of 401(k) plans. In ADD, higher match rates were generally associated on the extensive margin with a greater likelihood of saving something in IDAs and—on the intensive margin for those who saved something—a lower level of IDA savings.